Resveratrol Decreases Periodontal Breakdown and Modulates Local Levels of Cytokines During Periodontitis in Rats - Casati, Marcio Z. [UNESP]; Algayer, Carolina [UNESP]; Cruz, Geisa Cardoso da [UNESP]; Ribeiro, Fernanda V. [UNESP]; Casarin, Renato C. V. [UNESP]; Pimentel, Suzana P. [UNESP]; Cirano, Fabiano R. [UNESP] (Amer Acad Periodontology, 2013)
Background: Resveratrol (3,49,5-trihydroxystilbene) is a naturally occurring product found in numerous plants. Among its biologic properties, resveratrol may promote immunomodulatory effects on the host response. This study investigates the effect of continuous administration of resveratrol on the progression of experimental periodontitis in rats.Methods: Periodontitis was induced in rats in one of the first molars chosen to receive a ligature. Animals were assigned to one of two groups: 1) daily administration of the placebo solution (control group) or 2) 10 mg/kg resveratrol (RESV group). The therapies were administered systemically for 30 days: for 19 days before periodontitis induction and then for another 11 days. Then, the specimens were processed for morphometric analysis of bone loss, and the gingival tissue surrounding the first molar was collected for quantification of interleukin (IL)-1 beta, IL-4, and IL-17 using a multiplexing assay.Results: Intergroup comparisons of the morphometric outcomes revealed higher bone loss values in ligated molars and unligated teeth in the control group than the RESV group (P < 0.05). The immunoenzymatic assay of the gingival tissue showed a lower concentration of IL-17 in the RESV group than the control group (P < 0.05), whereas no differences in the IL-1 beta and IL-4 levels of the groups were observed (P > 0.05).Conclusions: Continuous administration of resveratrol may decrease periodontal breakdown induced experimentally in rats. In addition, lower levels of IL-17 were found in the RESV group. Future studies are important to confirm the mechanism through which resveratrol exerts its effects.
Keywords: Alveolar bone loss; anti-bacterial agents; anti-inflammatory agents; periodontitis; plants, medicinal; resveratrol